Job satisfaction and leadership behavior brief measures : a development and validation study (2023)
Purpose Job satisfaction and leadership behavior are recognized by the organizational world as fundamental elements that influence the overall effectiveness of a company. However, as the first step for an adequate intervention on any of these variables, i